The small heat‐shock protein αB‐crystallin is essential for the nuclear localization of Smad4: impact on pulmonary fibrosis. Issue 4 (March 2014) - Bellaye, Pierre‐Simon; Wettstein, Guillaume; Burgy, Olivier; Besnard, Valérie; Joannes, Audrey; Colas, Julien; Causse, Sébastien; Marchal‐Somme, Joëlle; Fabre, Aurélie; Crestani, Bruno; Kolb, Martin; Gauldie, Jack; et al.
Abstract Idiopathic pulmonary fibrosis (IPF) is a devastating disease characterized by the proliferation of myofibroblasts and the accumulation of extracellular matrix (ECM) in the lungs. TGF‐β1 is the major profibrotic cytokine involved in IPF and is responsible for myofibroblast proliferation and differentiation and ECM synthesis. αB‐crystallin is constitutively expressed in the lungs and is inducible by stress, acts as a chaperone and is known to play a role in cell cytoskeleton architecture homeostasis. The role of αB‐crystallin in fibrogenesis remains unknown. The principal signalling pathway involved in this process is the Smad‐dependent pathway. We demonstrate here that αB‐crystallin is strongly expressed in fibrotic lung tissue from IPF patients and in vivo rodent models of pulmonary fibrosis. We also show that αB‐crystallin‐deficient mice are protected from bleomycin‐induced fibrosis. Similar protection from fibrosis was observed in αB‐crystallin KO mice after transient adenoviral‐mediated over‐expression of IL‐1β or TGF‐β1. We show in vitro in primary epithelial cells and fibroblasts that αB‐crystallin increases the nuclear localization of Smad4, thereby enhancing the TGF‐β1–Smad pathway and the consequent activation of TGF‐β1 downstream genes. αB‐crystallin over‐expression disrupts Smad4 mono‐ubiquitination by interacting with its E3–ubiquitin ligase, TIF1γ, thus limiting its nuclear export. Conversely, in the absence of αB‐crystallin, TIF1γ can freely interact with Smad4. Consequently, Smad4 mono‐ubiquitination and nuclear export are favoured and thus TGF‐β1–Smad4 pro‐fibrotic activity is inhibited. This study demonstrates that αB‐crystallin may be a key target for the development of specific drugs in the treatment of IPF or other fibrotic diseases. Copyright © 2013 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.